Validation of modified World Health Organization classification for pregnant women with heart disease in a tertiary care center in southern Thailand - Suwanrath C; Thongphanang P; Pinjaroen S; Suwanugsorn S (Dove Medical Press, 2018)
Chitkasaem Suwanrath,1 Putthaporn Thongphanang,1 Sutham Pinjaroen,1 Saranyou Suwanugsorn2 1Department of Obstetrics and Gynecology, 2Department of Internal Medicine, Faculty of Medicine, Prince of Songkla University, Hat Yai, Songkhla, Thailand Purpose: To validate the modified World Health Organization (WHO) classification in pregnant women with congenital and acquired heart diseases. Patients and methods: The database of pregnant women with heart disease, who delivered at Songklanagarind Hospital between January 1995 and December 2016, was retrieved from the Statistical Unit, Department of Obstetrics and Gynecology, along with the Hospital Information System of Songklanagarind Hospital, Faculty of Medicine, Prince of Songkla University. Each patient was retrospectively classified according to the modified WHO classification of maternal cardiovascular risk. Comparison of maternal and fetal outcomes among the modified WHO classes were analyzed using the chi-square test or Fisher’s exact test and one-way ANOVA test. A p-value of <0.05 was considered statistically significant. Results: A total of 331 cases were studied: 157 cases with congenital heart disease and 174 cases with acquired heart disease. There were 48, 173, 32 and 78 cases in the modified WHO class I, II, III and IV, respectively. Congestive heart failure was the most common complication. The overall maternal mortality rate was 3.6%, all of which were in the modified WHO class IV. Maternal cardiovascular events occurred in 24.2% of cases, increasing rates with higher modified WHO class: 4.2%, 15.0%, 25.0% and 56.4% in class I, II, III and IV, respectively (p<0.001). Adverse fetal outcomes including preterm delivery, low birth weight, small for gestational age and neonatal intensive care unit admission were also significantly increased in class III and IV (p<0.05). Conclusion: The modified WHO classification is useful not only for obtaining a cardiovascular risk assessment in pregnant women with heart disease but also for predicting adverse fetal outcomes. It must, therefore, be implemented into routine care service at all levels of health care systems. Keywords: heart disease, cardiovascular complications, pregnancy, heart failure, maternal mortality